Delivery of Retained Second Twin in Case of Omphalopagus Conjoined Twins: Abdominovaginal Approach - Wondimagegnehu Sisay Woldeyes (Hindawi Limited, 2018)
Conjoined twin is a rare complication of monozygotic twins resulting from incomplete splitting of an embryo into two separate twins or early secondary fusion of two originally separated embryos. When diagnosed at early gestation, one can get adequate time to counsel the family on whether to continue with the pregnancy and proper intervention can be planned. On the other hand, undiagnosed cases may be first recognized in labor after they have caused labor-related complications. In the present case report, an undiagnosed case of a conjoined twin has presented in labor followed by delivery of one baby with the retention of the second baby. This presented a unique challenge to the managing team and required hysterotomy to effect delivery of the unborn baby. We report this case to highlight the importance of early diagnosis of a conjoined twin. On another hand where this does not happen and a conjoined twin is suspected for the first time after it has caused labor-related complications, the management should be individualized based on the clinical circumstance.